Enhancing English Listening Skills through Metacognitive Strategy: A Study on Student Achievement - Nasution, Zuraidah; Prihatini, Syafrina (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study investigates the significant effect of metacognitive strategy instruction on students’ achievement in listening comprehension among eighth-grade students at SMP Muhammadiyah 7 Medan during the 2022/2023 academic year. The population consisted of 60 students, divided into an experimental group taught using metacognitive strategies and a control group taught by conventional methods. Employing a quantitative descriptive design, data were collected through multiple-choice and essay listening tests and analyzed using an independent samples t-test. The results demonstrated a statistically significant improvement in the experimental group’s listening comprehension compared to the control group (t₀ = 15.52 > tₜ = 2.00, p < 0.05, df = 94). This finding aligns with contemporary research highlighting that metacognitive strategies—such as planning, monitoring, and evaluating listening processes—enhance learners’ ability to manage comprehension challenges and improve performance (Aktar, 2020). The study confirms that teaching metacognitive strategies fosters greater learner autonomy, motivation, and effective listening skills, particularly in second language contexts where learners face difficulties such as limited vocabulary and lack of exposure to native speakers. Implications suggest that integrating metacognitive strategy instruction into listening curricula can significantly boost students’ listening achievement and overall language proficiency.